Cervical disc herniations: When to fuse? - (:unkn) unknown (SPRINGER WIEN, 2000)
The choice of surgical treatment for cervical disc herniations is still controversial. The objective of this retrospective study is to compare the clinical and radiological results after cervical discectomy with and without fusion. Clinical and radiological status after anterior cervical discectomy with and without fusion in 160 cases were reviewed. Clinical outcome analysis was performed using modified Prolo's scale. Overall outcome showed a 86.9% good outcome. The rate of good outcome after anterior cervical discectomy (ACD) and anterior cervical discectomy with fusion (ACDF) was 86.3% and 85.7%, respectively. There was no difference between Prolo's scales of patients treated with ACD and ACDH (p > 0.05). The mean Prolo's score in patients with one-level and two-level cervical disc herniation treated with ACD was 8.746 +/- 0.983 and 6.600 +/- 1.174 (p < 0.0001), whereas the mean Prolo's scores after one-level, two-level, and three-level discectomy with fusion (ACDF) was 8.307 +/- 0.630, 8.428 +/- 1.390, and 7,750 +/- 1.389, respectively (p > 0.05). Comparison of Prolo's scores of patients with one-level cervical disc herniation underwent ACD and ACDH showed no significant difference (p > 0.05), whereas there was a significant difference between Prolo's scores of patients with two-level cervical disc herniation who underwent ACD and ACDF (p < 0.0001). The overall fusion rate was 69%. The fusion rate was 64.3% and 89.2% after ACD and ACDF, respectively (p < 0.05). These results showed that a fusion procedure is not necessary for one-level cervical discectomy.
Keywords: cervical disc herniation; anterior cervical discectomy; interbody fusion; INTERBODY BONE GRAFT; TERM FOLLOW-UP; ANTERIOR DISCECTOMY; ILIAC BONE; FUSION; DISKECTOMY; DISEASE; RADICULOPATHY; COMPLICATIONS; MYELOPATHY